Re‐evaluation of pullulan (E 1204) as a food additive and new application for its extension of use - EFSA Panel on Food Additives and Flavourings (FAF); Laurence Castle; Monica Andreassen; Gabriele Aquilina; Maria Lourdes Bastos; Polly Boon; Biagio Fallico; Reginald Fitzgerald; Maria Jose Frutos Fernandez; Bettina Grasl‐Kraupp; Ursula Gundert‐Remy; Rainer Gürtler; et al. (EFSA Journal)
Abstract The present opinion deals with the re‐evaluation of pullulan (E 1204) when used as a food additive and with the new application on the extension of use to several food categories. Pullulan (E 1204) is obtained by fermentation of a food‐grade hydrolysed starch with non‐genetically modified Aureobasidium pullulans ■■■■■. Based on the available information, the Panel considered that the manufacturing process of pullulan (E 1204) using this microorganism does not raise a safety concern. The Panel confirmed that pullulan (E 1204) is of no concern for genotoxicity. In vitro, pullulan (E 1204) is broken down by salivary and pancreatic amylase and intestinal iso‐amylase and it is further metabolised to short chain fatty acids in the colon by fermentation. Human adult volunteer studies suggested that effects of pullulan (E 1204) are similar to the effects of other poorly digestible carbohydrate polymers including modified celluloses and that mild undesirable gastrointestinal symptoms (i.e. abdominal fullness, flatulence, bloating and cramping) may occur at doses of 10 g pullulan per day and greater. The Panel compared the dose of 10 g pullulan per day with the dietary exposure estimates to pullulan (E 1204) in its currently permitted uses and considering the proposed changes to the currently permitted uses. The Panel concluded that there is no need for a numerical ADI for pullulan (E 1204) and there is no safety concern for the currently reported uses and use levels. Additionally, the Panel concluded that the exposure estimates considering the proposed changes to the currently permitted uses and use levels of pullulan (E 1204) are of no safety concern. The estimates for dietary exposure to pullulan (E 1204) indicate that individuals with a high level of exposure, principally coming from food supplements, may experience mild gastrointestinal symptoms at the currently reported uses and use levels.